PERANCANGAN WEB DESIGN SHOPPING CENTRE PUTRI MINANG DI KOTO TUO KABUPATEN TANAH DATAR - SUCI RAHMADANI, Drs. Syafwandi, M.Sn, Eliya Pebriyeni, S.Pd., M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2014)
Putri Minang shopping center is one of the local craft shopping center Minangkabau are in Koto Tuo Tanah Datar. Founded in 1995 by Mr. H. Edi Yuswir, BSc, is a shopping center located on the highway Padang-Bukittinggi Km length. 5. Named Putri Minang with background embroidery crafts and crafts made by local girls Minangkabau. Promotion ever conducted only through travel agents. Promotion through the travel agent for this less reach the target audience, therefore they invented design promotional shopping center Putri Minang through the media website with the aim of promoting and introducing a shopping center that provides craft Minangkabau, because the web can reach the whole world, thereby limiting effect in an effort to achieve a purpose. Designing web design as a major media campaign Putri Minang shopping center, then through media support, the necessary data analysis through 5W + 1H. This method is needed to strengthen and enhance the design.Keywords: Web Design, Local Handicrafts, Shopping Centre, Putri Minang